The temporal topography of the N-Methyl- N-nitrosourea induced photoreceptor degeneration in mouse retina - Tao, Ye (Sci Rep, 2015)
Retinitis pigmentosa (RP) is a group of inherited neurodegenerative diseases characterized by the progressive photoreceptors apoptosis. The N-Methyl- N-nitrosourea (MNU) is an alkylating toxicant which could induce photoreceptor apoptosis resembling that of the hereditary RP. However, the detailed process pattern of this degeneration remains poorly characterized. We systemically explored the topography of the photoreceptor degeneration in the MNU treated mouse, and related these spatial data with the time-dependent characteristics of retinal pathology. These temporal topographic data delineated sequential scenes of the progressive photoreceptor degeneration in the MNU treated retinas: focal photoreceptors showed different vulnerabilities to the MNU toxicity and displayed a distinctive spatial- and time-dependent progression. Moreover, the positional asymmetry between the retinal quadrants firstly provided instructive information about the unique toxicology properties of the MNU. Further mechanism study suggested that the up-regulation of Bax and Calpain-2, rather than the Caspase-3, should be responsible for the asymmetry in the MNU induced photoreceptor degeneration. Together with the comparative sensitivities to the neurotoxicity of MNU between two photoreceptor populations, these topographic data would facilitate the standardization of analytic parameters related to the MNU induced RP model, and enhance its application in the therapeutic explorations of human RP.